2022
DOI: 10.1002/aenm.202202704
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Low‐n Ruddlesden‐Popper Formamidinium‐Based Perovskite for Efficient and Air Stable Solar Cells

Abstract: The relatively lower crystallinity and random orientation of quantum well structures hinder carrier transport and limit the performance of formamidinium (FA) based low‐n 2D perovskite devices. In this work, the crystallization and quantum well orientation are fine tuned to achieve efficient low‐n FA based Ruddlesden–Popper perovskite solar cells. The effects of different ionic additives on the crystallization, orientation, and photovoltaic performance of FA based low‐n 2D perovskites are comparatively investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
1
30
0
1
Order By: Relevance
“…According to the above results, the data shows that the 2D perovskite grown on NiO x /KPF 6 substrates has better crystallinity, which is helpful for the fabrication of efficient PSCs. [39,40] Figure 3b shows that perovskite films with and without KPF 6 modification have similar ultraviolet-visible (UV-vis) absorption spectra. This indicates that the bandgap of 2D perovskite does not change due to KPF 6 modification.…”
Section: Resultsmentioning
confidence: 99%
“…According to the above results, the data shows that the 2D perovskite grown on NiO x /KPF 6 substrates has better crystallinity, which is helpful for the fabrication of efficient PSCs. [39,40] Figure 3b shows that perovskite films with and without KPF 6 modification have similar ultraviolet-visible (UV-vis) absorption spectra. This indicates that the bandgap of 2D perovskite does not change due to KPF 6 modification.…”
Section: Resultsmentioning
confidence: 99%
“…NH 4 SCN has realized similar stability improvements in other reports. 522 Likewise, the crystallinity of the ACI halide perovskite GA 3 MA 3 Pb 3 I 10 (GA = guanadinium) was enhanced by the incorporation of MASCN, and grain boundary defects were simultaneously passivated by the partial substitution of MA with PEA, improving stability both in ambient air and at 85 °C in N 2 atmosphere. 523 Chen et al observed that replacing either MAI with MACl or PEAI with PEACl in precursor solutions of PEA ⟨n⟩ ≥ 6 RP halide perovskite significantly improved crystallinity, reduced defect density, and enhanced device stability in inert atmosphere.…”
Section: Strengthen Interlayer Interactionsmentioning
confidence: 99%
“…Similar to 3D halide perovskites, defect passivation and improvements in crystallinity can suppress defect-mediated degradation pathways in 2D halide perovskites and improve device stability. Yukta et al demonstrated an improvement in unencapsulated device stability both at RT/60%RH and at 85 °C, as well as an increased water contact angle, for (NDA)(MA) 3 Pb 4 I 13 (NDA = 1,5-diamino­naphthalene, n = 4) treated with NH 4 SCN . The improvement in stability was attributed to a reduced defect concentration and increased crystallinity as a result of the addition of NH 4 SCN, which regulates crystal growth and suppresses defects through the synergistic occupation of A-sites by NH 4 + and X-sites by SCN – .…”
Section: Stability Of 3d and 2d Halide Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for mixed-dimensional HP solar cells of [n] ≤ 4, a PCE benchmark of 18.2% has been reached early in 2018 and stranded ever since. 26 A very recent work of influence reported a PCE of 18.14%, 43 and the greatest value ever reported is merely 18.42%. 44 Therefore, model II may not be accurate enough to describe the working mechanism of mixeddimensional 2D/3D HP solar cells.…”
Section: Photophysical Model IImentioning
confidence: 99%